2009
DOI: 10.1016/j.bpj.2009.01.062
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature Dependence of Lipid Membrane Permeability, its Quantized Nature, and the Influence of Anesthetics

Abstract: We investigate the permeability of lipid membranes for fluorescence dyes and ions. We find that permeability reaches a maximum close to the chain melting transition of the membranes. Close to transitions, fluctuations in area and compressibility are high, leading to an increased likelihood of spontaneous lipid pore formation. Fluorescence correlation spectroscopy reveals the permeability for rhodamine dyes across 100-nm vesicles. Using fluorescence correlation spectroscopy, we find that the permeability of ves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
254
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(276 citation statements)
references
References 59 publications
19
254
1
2
Order By: Relevance
“…In support of the indirect pathway, it has been proposed (21), and supported by statistical thermodynamics (3,22) and coarse-grain modeling (23), that alcohol changes the lateral pressure within the membrane and that this increase can bias ion channels toward the closed state. In support of the direct pathway it has be shown that both ethanol (24) and other anesthetics (25) can change the permeability of lipid membranes.…”
Section: Introductionmentioning
confidence: 95%
“…In support of the indirect pathway, it has been proposed (21), and supported by statistical thermodynamics (3,22) and coarse-grain modeling (23), that alcohol changes the lateral pressure within the membrane and that this increase can bias ion channels toward the closed state. In support of the direct pathway it has be shown that both ethanol (24) and other anesthetics (25) can change the permeability of lipid membranes.…”
Section: Introductionmentioning
confidence: 95%
“…There are no reports on neuronal growth in temperature microgradients in the literature, but it is known that bulk neuronal development is temperature-dependent (Ishida and Cheng, 1991;Fukui et al, 1992), and that some organisms (nematodes) have been shown to be extremely temperature sensitive, exhibiting thermotaxis up temperature gradients as small as 10 −4 • C/cm (Pline et al, 1988). It also seems that depolarization of the neuronal membrane is highly dependent on small variations in thermodynamic variables like temperature (Wunderlich et al, 2009;Blicher et al, 2009;Andersen et al, 2009;Wodzinska et al, 2009).…”
Section: Potential Trp Channel Activation In Optical Neuronal Guidancementioning
confidence: 99%
“…It has been shown that chemical guidance of growth cones is mediated by an asymmetric influx of calcium ions Ca 2+ ) and the neuronal transient receptor potential (TRP) channels appear to be the key sensors and mediators in the process (Wang and Poo, 2005;Talavera et al, 2008;Li et al, 2005;Sappington et al, 2009). It is know that TRP channels can be activated by depolarization of the cell using chemical guidance factors or by an increase in temperature (Talavera et al, 2008;Caterina et al, 1997) and highly localized heating (Huang et al, 2010), and there is strong evidence in general that depolarization of the neuronal membrane is highly sensitive to small variations in thermodynamic variables like temperature and pressure (Wunderlich et al, 2009;Blicher et al, 2009;Andersen et al, 2009;Wodzinska et al, 2009). We therefore propose the hypothesis that the optical neuronal guidance is mediated by laser-induced heating, in particular by influx of Ca 2+ -ions due to heat-induced activation of neuronal TRP channels, discussed more thoroughly in Section 4.1.…”
Section: Introductionmentioning
confidence: 99%
“…For further details the reader is referred to Refs. [8] and [9]. Our bilayer membrane was made up of dioleoyl-phosphatidylcholine (DOPC) and dipalmitoyl phosphatidylcholine (DPPC) in a 2:1 ratio.…”
Section: Introductionmentioning
confidence: 99%